2018
DOI: 10.1016/j.athoracsur.2018.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Lobectomy Versus Sublobectomy in Metachronous Second Primary Lung Cancer: A Propensity Score Study

Abstract: This study indicates that lobectomy is still a valid choice for MSPLC. Sublobectomy has value and shows equivalency in tumors sized 2 cm or smaller. For patients with advanced disease or at high risk, additional studies are needed to explore the value of sublobectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 27 publications
8
26
0
Order By: Relevance
“…The SEER database is a population-based tumor epidemiology database in the United States, covering about 28% of the population, including thousands of cases of lung cancers since 1973, therefore the SEER database is of great help in the study of lung cancer and other tumors (Yang et al, 2017; Yang et al, 2018). By analyzing the cases in the entire population of the SEER database, it is possible to effectively avoid the bias of the patients from the research given by a single institution.…”
Section: Discussionmentioning
confidence: 99%
“…The SEER database is a population-based tumor epidemiology database in the United States, covering about 28% of the population, including thousands of cases of lung cancers since 1973, therefore the SEER database is of great help in the study of lung cancer and other tumors (Yang et al, 2017; Yang et al, 2018). By analyzing the cases in the entire population of the SEER database, it is possible to effectively avoid the bias of the patients from the research given by a single institution.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al found that age, sex, tumor size, nodal stage, extent of surgery (lobectomy vs. sublobectomy), year of diagnosis, histologic type, and pathologic stage of the initial cancer were prognostic predictors of long-term survival in multiple primary lung cancer. 21 This study by Yang et al is the largest performed to date, but the proportions of anatomic/nonanatomic resections were not detailed in the sublobectomy group, preoperative lung function tests and intraoperative lymphadenectomy were not reported, and 20% of the patients in the cohort were treated for ipsilateral lesions. 20 Some previous studies focused specifically on bilateral surgery for multiple primary lung cancer, with much smaller population samples, and found no differences in survival between resection types or histologic features.…”
Section: Discussionmentioning
confidence: 95%
“…17,18,20 A recent study involving a propensity score analysis of 454 pairs of matched patients revealed better long-term survival outcomes for patients treated by bilateral lobectomy than for those treated by sublobectomy, particularly for stage I multiple primary lung cancer, following a first resection performed by lobectomy in 85% of patients, and including mostly bilateral lesions (80 vs. 20% ipsilateral). 21 However, the proportions of anatomic segmentectomy and nonanatomic sublobar resection among the interventions were unknown for the sublobectomy group. 21 Only Hattori et al have analyzed the risk factors of inhospital death (early postoperative mortality).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sublobectomy is defined as the extent of resection less than a lobe either requiring dissection of sectional vascular and bronchus or not ( Fig. 1), including segmentectomy and wedge resection [13]. The patient was placed in the full lateral decubitus position under general anesthesia with selective one-lung ventilation.…”
Section: Operation Techniquesmentioning
confidence: 99%